RSPEED：the reliability and real-time routing based on uncertain delay in wireless sensor network - Quan CHEN; Hong GAO (Tongxin xuebao)
The forwarding reliability was proposed by considering the unreliability and the delay of a link,and with which,a novel real-time routing protocol(RSPEED) was designed.The forwarding reliability denoted the probability to deliver the data successfully to the neighbor node under a given deadline,and it was used to achieve probabilistic QoS guarantee in timeliness and reliability.The protocol can also make trade-off between the transmission delay and the reliability of transmission to improve the probability of successful transmission when the environment and link quality is very poor.The experimental results show that the proposed approach can significantly improve the reliability of transmission and reduces the number of the missed deadline,and even when the channel is very poor,it can achieve 20% higher performance than SPEED.